Challenges for the Implementation of the China–Pakistan Economic Corridor (CPEC) : Economic, Political, and Security Aspects - Havlíčková, Klára (2025)
This thesis examines the challenges that pose a challenge to the implementation and long-term sustainability of the China-Pakistan Economic Corridor (CPEC) project, which is part of China's Belt and Road Initiative. CPEC aims to improve infrastructure, trade and transport links between China and Pakistan, encourage economic development and provide China with access to the Arabian Sea. Despite its potential, the project faces challenges that the thesis divides into three factors: economic, political and security. The economic section focuses on the cost of the projects, delays in their implementation and trade between Pakistan and China. The political part examines political instability and corruption. The last security part focuses on the increasing number of terrorist attacks, especially in the province of Balochistan. The thesis also mentions regional instability, particularly in Afghanistan. The findings show that while CPEC represents a development opportunity for Pakistan, its success is challenged by economic, political and security factors. Therefore, addressing these problems will be crucial to the successful implementation of CPEC and its long-term sustainability.